The Common Causes of Preterm Deliveries in Obstetric Patients - Gul, Hina; Magsi, Shahida Inayat; Shaikh, Aqsa (Biological and Clinical Sciences Research Journal, 2025)
Preterm delivery, defined as childbirth before 37 completed weeks of gestation, remains a major contributor to neonatal morbidity and mortality globally. Understanding the common causes is crucial for implementing preventive and management strategies tailored to high-risk populations. Objective: To identify and evaluate the common causes of preterm deliveries in obstetric patients. Methods: This descriptive cross-sectional study was conducted at Shaikh Zayed Women Hospital Larkana. over a period of June 2024 to December 2024. A total of 245 obstetric patients who delivered preterm were enrolled using non-probability consecutive sampling. Relevant clinical, demographic, and obstetric data were collected using structured proformas. The frequency and distribution of known etiological factors such as spontaneous preterm labor, PPROM, hypertensive disorders, infections, and multiple gestations were analyzed. Results: Out of 245 obstetric patients who delivered preterm, the most common cause was spontaneous preterm labor (36.3%), followed by PPROM (28.2%) and hypertensive disorders (18.8%). PPROM was frequently associated with urinary and genital infections. Hypertensive disorders were significantly more prevalent among women aged over 30 years (p = 0.03). Obese women (BMI ≥30) had higher rates of cesarean delivery (52.9%) and postpartum hemorrhage (19.1%). Neonatal outcomes were significantly worse in babies delivered before 34 weeks, with low birth weight seen in 86.5% and NICU admission in 58.3% of early preterm births. These associations were statistically significant (p < 0.001). Conclusion: Spontaneous preterm labor and PPROM were the leading causes of preterm deliveries in this population. Hypertension, infections, and multiple gestations were also notable contributors. Targeted antenatal surveillance and early intervention strategies are essential to mitigate these risks and reduce the burden of preterm birth.